Anchoring of long-term inflation expectations: Do inflation target formulations matter? - Christoph Große Steffen (ZBW - Leibniz Information Centre for Economics, 2021)
We use a novel anchoring-measure based on the distribution across professional forecasters' point forecasts to test empirically whether target formulations matter for the anchoring of long-term inflation expectations. In a panel of 29 countries, we find that the formulation of a point target increases the degree of anchoring compared with countries with a mere quantitative definition of price stability. A point target is more sucessful in limiting upside risks to inflation, while a range target allows for higher downside risk to the inflation outlook. Our results suggest that range targets and tolerance bands are interpreted by professional forecasters as zones where policy is less active.
Keywords: E42; E52; D84; 330; monetary policy; inflation targeting; inflation risk; expectations anchoring